Communication in the Elderly Family Development Program in Gresik Regency: Komunikasi Dalam Program Bina Keluarga Lansia di Kabupaten Gresik - Laili, Etri Nur; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe the implementation of the elderly family development program in Mulung Village, Driyorejo District, Gresik Regency. The method used in this research is descriptive qualitative through interviews, observation and documentation. The determination of the informants was carried out using a purposive sampling method which involved the midwife in charge at the Puskesmas, implementing nurses, village officials, cadres, and the community. Data analysis techniques using Miles and Huberman through data collection, data reduction, data presentation, and drawing conclusions. This study shows that the communication of the elderly family development program runs in accordance with the policies that have been determined by the PP and PA KB Office in collaboration with the Driyorejo Health Center to implement the program in each village. By using Edward III's theory which focuses on the communication dimension consisting of transmission, regular socialization needs to be improved so that the public can know the existence of the program, clarity of understanding can be accepted by policy implementers and consistency is proven by setting an examination schedule so that the health of the elderly can run well.